2014
DOI: 10.1007/s13197-014-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical analysis of Psophocarpus tetragonolobus (L.) DC seeds with fatty acids and total lipids compositions

Abstract: Psophocarpus tetragonolobus (L.) DC. is a tropical legume with potential nutritional properties. In present study, the physical properties and proximate composition of the seeds were evaluated. Besides, the physico-chemical properties of fatty oil from fully mature seeds were also studied. The fatty oil compositions of immature, mature and fully mature seeds were evaluated by GC-FID, GC/MS and 1 H-NMR. The study revealed that, fatty oil from fully mature seeds contained high proportion of unsaturated fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…ese results are similar to those of previous studies that reported between 23 and 40% [4,22] and 28.87 ± 0.45 in a study conducted by Wan Mohtar et al [3], but low when compared to other studies involving cowpea and wheat flours, where values ranged from 57.35% to 83.60% [23] with wheat flour having the highest carbohydrate content (83.60%). In this study, the carbohydrate content of the flours cannot be compared to that of cowpea (57.17%) and wheat flours (74.22%) reported by Ahmed et al [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ese results are similar to those of previous studies that reported between 23 and 40% [4,22] and 28.87 ± 0.45 in a study conducted by Wan Mohtar et al [3], but low when compared to other studies involving cowpea and wheat flours, where values ranged from 57.35% to 83.60% [23] with wheat flour having the highest carbohydrate content (83.60%). In this study, the carbohydrate content of the flours cannot be compared to that of cowpea (57.17%) and wheat flours (74.22%) reported by Ahmed et al [24].…”
Section: Discussionsupporting
confidence: 90%
“…Winged bean seeds are generating unique research and commercial interest mainly due to their nutritional quality (high proteins and fatty oil content). Plant parts such as flowers, leaves, green pods, and tubers are also suitable for consumption [4].…”
Section: Introductionmentioning
confidence: 99%
“…Winged bean plant is appreciated for the high nutrients composition, especially with respect to proteins, vitamins and minerals; the tubers are starchy with high percentage of proteins 17 to 20% (by weight) compared to other vegetables, the leaves and flowers contain from 5 to 15% proteins (by weight), the seeds are highly nutritious with 32 to 37% proteins, which is similar to the amount of proteins found in soy beans and higher than that found in other beans [26]. The seeds also contain 23 to 40% carbohydrates [8,28,29], vitamins like vitamin B 1 , B 2 , B 3 , B 6 , B 9 and in vitamins C, A and E. The mature seeds contain 14 to 25% fats by weight, of which 94% are in free form, whereas the rest are complexed with carbohydrates and proteins [29].…”
Section: Nutrient Compositionmentioning
confidence: 86%
“…Winged bean is rich in minerals including calcium, iron, phosphorous, potassium, sulfur, sodium, magnesium, zinc, manganese, boron, barium, copper, chromium and strontium [28,30,31]. Psophocarpus tetragonolobus contains 54 to 75% of unsaturated fatty acids, of which 38.6% are mono-unsaturated and 36.9% are polyunsaturated [29,32], and no trans fatty acids are found. Winged bean oil contains 30 to 40% saturated fatty acids which represent more than the content observed in soybean [33].…”
Section: Nutrient Compositionmentioning
confidence: 99%
“…Winged bean seed contains high dietary protein due to its amino-acid content, substantial protein bioavailability, and low antinutritional factors [80]. The carbohydrate content in unprocessed winged bean seed is higher than in processed winged bean seed [81]. The moderate carbohydrate content in winged bean flour makes it a good source of energy in breakfast formulations.…”
Section: Winged Bean (Psophocarpus Tetragonolobus)mentioning
confidence: 99%